2012
DOI: 10.1371/journal.pone.0048496
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Music: Integration of Auditory and Tactile Inputs in Musical Meter Perception

Abstract: Musicians often say that they not only hear, but also “feel” music. To explore the contribution of tactile information in “feeling” musical rhythm, we investigated the degree that auditory and tactile inputs are integrated in humans performing a musical meter recognition task. Subjects discriminated between two types of sequences, ‘duple’ (march-like rhythms) and ‘triple’ (waltz-like rhythms) presented in three conditions: 1) Unimodal inputs (auditory or tactile alone), 2) Various combinations of bimodal input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Meter is perceptible auditorily and tactually. Huang et al (2012) demonstrate that it is also possible to audio-tactually discriminate a novel musical meter that is present neither audibly nor tactually. 'We next show in the bimodal experiments that auditory and tactile cues are integrated to produce coherent meter percepts.'…”
Section: Grade 4: Multisensory Awareness Of Novel Feature Instancesmentioning
confidence: 94%
See 1 more Smart Citation
“…Meter is perceptible auditorily and tactually. Huang et al (2012) demonstrate that it is also possible to audio-tactually discriminate a novel musical meter that is present neither audibly nor tactually. 'We next show in the bimodal experiments that auditory and tactile cues are integrated to produce coherent meter percepts.'…”
Section: Grade 4: Multisensory Awareness Of Novel Feature Instancesmentioning
confidence: 94%
“…Huang et al () demonstrate that it is also possible to audio‐tactually discriminate a novel musical meter that is present neither audibly nor tactually. ‘We next show in the bimodal experiments that auditory and tactile cues are integrated to produce coherent meter percepts.’ They assert, ‘We believe that these results are the first demonstration of cross‐modal sensory grouping between any two senses’ (Huang et al, , p. 1). To illustrate this type of phenomenon, consider a simple case of intermodal meter perception using an audio‐tactual rhythm pattern.…”
Section: Grade 4: Multisensory Awareness Of Novel Feature Instancesmentioning
confidence: 99%
“…The auditory -tactile interactions play a particularly important role in music perception (Huang, et al, 2012) and their neural representation is more robust in humans with musical training (Kuchenbuch, et al, 2014). …”
Section: Multisensory Integration In the Auditory Cortexmentioning
confidence: 99%
“…Consider the case of intermodal meter perception. A study by Huang et al (2012) found that auditory and tactile sequences were coherently grouped by musically trained subjects performing a meter recognition task. Meter, however, can be perceived by means of either audition or touch alone.…”
Section: Generative Multisensory Integrationmentioning
confidence: 99%